PENGARUH MODEL PEMBELAJARAN TAKE AND GIVE BERBANTUAN APLIKASI CANVA TERHADAP MOTIVASI BELAJAR SISWA PADA MATERI BILANGAN KELAS 2 SD NEGERI 02 BUNAKEN - Juliana Margareta Sumilat; Denysa Caroles (STKIP Subang, 2025)
This study aims to examine the effect of the Take and Give learning model assisted by the Canva application on students' learning motivation in the topic of numbers in Grade 2 of SD Negeri 02 Bunaken. The Take and Give model emphasizes student-to-student interaction through information sharing, while Canva serves as a visual learning tool that enhances engagement and contextual learning. A quantitative approach with a quasi-experimental design was used. The research subjects were Grade 2 students divided into experimental and control groups. Instruments included a learning motivation questionnaire and observation sheets. Results show a significant increase in learning motivation among students in the experimental group compared to the control group. The study concludes that the Take and Give model assisted by Canva is effective in enhancing students’ motivation in learning numbers.